Far and wide: Exploring provider utilization of remote service provision for genome‐wide sequencing in Canada. Issue 10 (17th September 2021) - Enns, Emily A.; Wainstein, Tasha; Dragojlovic, Nick; Kopac, Nicola; Lynd, Larry D.; Elliott, Alison M.
Abstract: Background: In Canada, funding for genome‐wide sequencing (GWS; exome and whole genome) is provincially regulated. We characterized the uptake of GWS by genetics health professionals (GHPs) across Canada and describe how they use remote technologies for patient access to GWS and genomic counseling. Methods: We distributed a survey to 574 Canadian GHPs addressing: GWS use, remote technologies (e.g., telephone, videoconferencing) for GWS and provider opinions regarding these technologies. Data were summarized using descriptive statistics. Associations between variables were evaluated using Chi‐square and Fisher's Exact tests for categorical data, and t‐tests or Mann–Whitney U tests for continuous data. Results: Of 116 GHPs, 50% reported using GWS in the last year and 57% of GWS users reported using remote technologies. Clinical geneticists who did not use GWS reported lack of provincial funding as the principal reason. Remote technologies were most commonly used for informed consent and results, and rarely used for initial consultations. Average wait times for a GWS appointment were shorter for remote appointments (mean 44.2 (SD 40.2) weeks) than for in‐person (mean 58.2 (SD 42.9), p  = 0.036). Conclusion: The use of GWS varied across Canada, professional designation, and discipline. Funding remains a barrier to GWS access. Remote technologies increase patient access with reduced wait times. Abstract : Responses regarding genome‐wide sequencing use across Canada.